Factors influencing the efficiency of building materials self-cleaning with photocatalytically active components - P. I. Kiyko; T. N. Chernykh; V. P. Plesovskikh (Vestnik MGSU)
Introduction. The use of building materials with photocatalytically active additives is considered as a promising solution to environmental and economic problems of the urban environment. In the field of building materials science the necessity of studying the microstructure of self-cleaning building materials and the influence of impurities on the efficiency of self-cleaning of materials with photocatalytically active additives is determined.Materials and methods. Red gypsum (production waste with photocatalytically active impurities), cement, building gypsum, microsilica, synthesized photocatalytically active titanium oxide – silicon oxide additive, and iron-based pigments were used. Tablet specimens of gypsum-cement-pozzolanic binder with various photocatalytically active components were made: photocatalyst additive, pigments, photocatalytically active oxide impurities. The microstructure of the specimens and the distribution of titanium and iron elements were studied using scanning electron microscopy. The efficiency of self-cleaning was determined by the change in the contact angle of a water drop on a surface coated with oleic acid.Results. The efficiency of self-cleaning of specimens with added and impurity photocatalytically active components was determined. The influence of added impurities on the structure of the material and the influence of the type and concentration of impurities on the efficiency of self-cleaning were revealed.Conclusions. Titanium oxide photocatalyst additive at a concentration of 4.4 % provides high self-cleaning efficiency, evenly distributed throughout the material without affecting the structure of the forming binder stone. Pigment (iron (III) oxide) provides sufficient self-cleaning efficiency at a concentration of 2–9 %, at concentrations of more than 2 % it is distributed unevenly, providing a small increase in self-cleaning efficiency indicators. With the joint introduction of titanium and iron oxides, deterioration in self-purification is observed due to the high degree of recombination of electron – hole pairs. Red gypsum with impurity oxides of titanium and iron has shown a high efficiency of self-cleaning, has a uniform distribution of impurities that do not have a clear effect on the structure of the material.